The new species Gorytes mikhailovi sp. nov. from Kazakhstan with a key to the Palaearctic species of Gorytes Latreille, 1804 (Hymenoptera: Apoidea: Crabronidae) - Mokrousov, Mikhail V.; Proshchalykin, Maxim Yu. (Zootaxa, 2021)
Gorytes mikhailovi sp. nov. is described and illustrated from southeastern Kazakhstan (Zhambyl and Almaty Regions). The species groups of the Palaearctic Gorytes Latreille, 1804 (Hymenoptera: Apoidea: Crabronidae) are reviewed and an updated key to the Palaearctic species is provided.